PERENCANAAN DAN PELAKSANAAN TEBAL LAPIS PERKERASAN JALAN DI DESA SLADI, KECAMATAN PONJONG, KABUPATEN GUNUNGKIDUL. - , WAHYU LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As the requirement of transportation infrastructure that good is support factor the smooth running of economy also good and quickly transportation. In this matter require to be thought of to increase and developing to improve amenity access to an region or area. As the repair, improvement access road and opening of new road is believed by very useful to moving economics, and water down and quickening resident mobilization. Street Countryside Sanggrahan, Sladi, Ponjong, Gunungkidulregency is access roads which have a very important role to support economics sector and transportation infrastructure, so that Dinas Pekerjaan Umum Gunungkidul specialy Cipta Karya Area, doing planning of improvement to the smooth running transportation. Therefor, need in making of flexible pavement with Penetration Coat of Macadam (LAPEN). From result Analyse Calculation with system MAK (Method Analyse Component) get is thick of hard coat (D2 = 8,42 cm) with age plan 10 years where thickly hard coat of roads can support vehicle traffic capacities.